Motives for and Repercussions of Leaving the Amish Community by Amish Women in Crossing Over: One Woman’s Escape from Amish Life by Ruth Irene Garrett (Author) and Rick Frank (Contributor) - Ghezali, Baya Nassima; Kourdourl,i Abdelkader (University of Ammar Theledji -Laghouat, 2020)
Research on minority groups in the United States is important because it provides better understanding of the diverse cultures of these groups in American society. This dissertation undertakes the study of the Amish in the United States through their nascent literature. The study explores the issue of Amish woman’s departure from their communities towards the outer modern world. Moreover, the study sets two objectives: first, to explore the root causes which determine the Amish woman to leave her community, towards the outer modern world. Second, to show how her process of adaptation within the modern world. This is carried out through the analysis of the autobiography Crossing Over: One Woman's Escape from Amish Life by Ruth Irene Garrett. The research adopts the qualitative approach in collecting data and in analyzing data. One interpretation of the findings suggests that the Amish Church and tradition decisively shape the individual identity of Amish woman that they can construct or deconstruct this identity.